Hysteroscopy (Springer International Publishing, 2018)
This book offers a cutting-edge guide to hysteroscopy and provides readers with the latest and most essential information on procedure techniques, clinical advances and international developments in practice and treatment of endometrial pathology. Providing comprehensive coverage, it explains in detail every aspect of hysteroscopy, from diagnostics to hysteroscopic surgery. As such, it addresses the bases of hysteroscopy; pre-, intra- and post-hysteroscopy medications; intracavitary pathologies; fertility issues; and surgical implications and complications. At the same time, it also explores challenging and controversial topics, such as hysteroscopy and ART, submucous myomas, and uterine malformations. All topics are discussed by prominent experts in the field, and clearly organized and illustrated to help readers gain the most from each chapter. Accordingly, the book offers a valuable resource for all gynecologists working at hysteroscopy units, reproductive units, gynecological and oncological units, as well as a quick reference guide for all other physicians interested in the topic.